Significantly Reduced Radiation Exposure to Operators during Kyphoplasty and Vertebroplasty Procedures: Methods and Techniques - Ortiz, A.O.; Natarajan, V.; Gregorius, D.R.; Pollack, S. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Vertebroplasty and kyphoplasty can be associated with significant radiation exposure to the operator. We compared the exposure levels to an operator performing vertebral fracture augmentation with vertebroplasty and kyphoplasty, to assess a cement injection and a monitoring technique designed to reduce this exposure.METHODS: A neuroradiologist performed 189 consecutive vertebral augmentation procedures in 135 patients with osteoporotic compression fractures by using a bilateral approach with biplane pulse fluoroscopy at 7.5 pulses/second. Cement delivery was performed with intermittent fluoroscopy with kyphoplasty and vertebroplasty by using syringes or continous fluoroscopic monitoring with a cement delivery system (CDS). Data collection included time and operator exposure parameters.RESULTS: A total of 87 kyphoplasty procedures, 82 vertebroplasty procedures with a CDS (VP-CDS), and 20 vertebroplasty procedures with syringes (VP-S) were safely performed. Mean fluoroscopy time for device positioning was 4.3 minutes for each procedure type. Mean fluoroscopy time (minutes) for cement delivery was significantly different for the 3 procedure types; 2.1 for kyphoplasty, 3.7 for VP-CDS, and 1.5 for VP-S (P < .0001). Comparable mean radiation exposure rates (microsieverts/minute) were 0.8 for kyphoplasty, 1.1 for VP-CDS, and 0.3 for VP-S during device-positioning and 1.7 for kyphoplasty, 2.9 for VP-CDS, and 0.2 for VP-S during cement injection (P < .002).CONCLUSION: Use of the modified cement injection technique and intermittent fluoroscopy with kyphoplasty and vertebroplasty with syringes results in a significantly lower operator exposure rate compared with vertebroplasty with a CDS.